La Primera Guerra Mundial en el cine italiano:La grande guerra - Carlota Coronado Ruiz (Historia y Comunicación Social, 2005)
Mario Monicelli’s La grande guerra is the first Italian film to approach the delicate matter (In Italy) of the First World War. Until 1959, the year the film was made, First World War had been a subject excluded from the silver screen. The few films made showed an idilic vision of the war: the Italian soldier as a hero and Italy as a great power. Monicelli’s film caused a big scandal during the sixties: the first time such a tragic subject was made comic material. The film offers a magnificent representation of the Italian society and the moral and living conditions of the soldiers were in. It’s a essay about the war, it’s absurdity, horror and fear. A war which caused a moral wound in the Italian population, a war noone spoke aloud about, until this film was released.